Legality of Indonesian Cryptocurrency Trading in the Era of Globalization - Firmansyah; Muryanto, Yudho Taruno (MultiTech Publisher, 2024)
The rapid development of cryptocurrencies does not rule out the possibility of criminal activity. Crypto currency developers seize investors' assets, causing investors to lose their assets, which is commonly known as